Narrative review on the impact of social media influencers (SMIs) in shaping travel decision among Gen Z / Rosevia Francis - Francis, Rosevia (Faculty of Communication and Media Studies (FCMS), 2024)
Social media influencers (SMIs) have become significant players due to the exponential growth of digital platforms, especially when it comes to influencing Gen Z’s travel preferences and decisions. However, the pervasive influence of social media influencers (SMIs) on Gen Z’s travel decisions presents a contemporary challenge for marketers and tourism professionals as this generation seems to be disengaging from traditional advertising, favoring influencer marketing as a more potent means of endorsement that can influence travel decision-making processes. The lack of a comprehensive analysis on how these influencers specifically shape the travel choices of Gen Z’s poses a significant problem in navigating the evolving landscape of travelrelated content consumption. Therefore, the purpose of this study is to explore the impact of social media influencers (SMIs) on shaping travel decisions among Gen Z’s. The approach developed for this study is qualitative content analysis based on secondary data collected from online sources, with a total of 10 articles chosen carefully after going through some selection criteria process. Key findings highlight the pivotal role of authenticity, whereas the positive correlation between perceived authenticity, trust, and engagement among Gen Z. The discussion explores the implications of these findings on Gen Z's travel decision-making, providing insights for marketers, influencers, and researchers.